Antara Hukum dan Realitas Sosial: Studi Empiris tentang Pencegahan Pernikahan Dini melalui Pelibatan Keluarga dan Masyarakat - M. Rifqi Ahrar M; Muhammad Akmal; Abdurrahman Rahman; Muh. Muhsin (IAI DDI Mangkoso, 2026)
Early Marriage remains a social Problem that Frequently occurs in rural areas, including sondoang village, kalukku district, mamuju regency. The practice of early marriage is influenced by various factors such as family economic condition, low level of education, cultural values, and the limited understanding of parents and the community regarding the negative impacts of early marriage on children. This study aims to describe the role of parents and the community in preventing early marriage in sondoang village. This research employed a qualitative method with a descriptive approach. Data were collected through in-depth interviews, observation, and documentation involving parents, adolescent, community leaders, religious leaders, and village officials as informants. The result indicate that parents play an important role in providing education, supervision, and affective communication with their children regarding future planning and the risks of early marriage. Meanwhile, the community contributes through socialization programs, counseling, and the establishment of social norms that support delaying the age of marriage. However, these efforts still face several obstacles, including limited knowledge and strong cultural influences. Therefore, synergy among parents, the community, and the village government is essential to strengthen sustainable early marriage prevention efforts